Kompatibilitas Bacillus spp. dan Aktinomiset sebagai Agens Hayati Xanthomonas oryzae pv. oryzae dan Pemacu Pertumbuhan Padi - Candra Putra; Giyanto Giyanto (Jurnal Fitopatologi Indonesia, 2014)
Bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae is an important disease on rice. The bacteria is seed borne and survives for a long time in the seed. Some beneficial microbes, such as Bacillus spp. and actinomycetes has been reported as biocontrol agents for the disease. The objectives of the research was to select isolates of actinomycetes as biocontrol agents for X. oryzae pv. oryzae which is also compatible with Bacillus spp. by seed application. Actinomycetes isolated from soil was selected using dual culture method on agar medium and on growing medium composing of mixture of soil and manure (1:1 w/w). Three isolates out of 16 isolated actinomycetes, i.e. APS 7, APS 9, and APS 12 showed antagonistic activities against X. oryzae pv. oryzae and compatible with Bacillus spp. Both Bacillus spp. and actinomycetes was applied to rice seed variety Ciherang using seed coating method in formulation containing rice husk. Actinomycetes treatment using APS 9 isolate was able to suppress population of X. oryzae pv. oryzae by (88.89%) and induce crown growth by 36.13%. The highest percentage of seedling emergence was obtained on combination treatment of B12 + APS 7 and single treatment of APS 9, i.e. 83.33% and 79%, respectively and significantly different with those of control treatment (56.67%). Application of Bacillus spp. and actinomycetes on rice seed was able to suppress population of X. oryzae pv. oryzae on rice seedling and induce rice growth.